2016
DOI: 10.1159/000446907
|View full text |Cite
|
Sign up to set email alerts
|

Fish Neurogenesis in Context: Assessing Environmental Influences on Brain Plasticity within a Highly Labile Physiology and Morphology

Abstract: Fish have unusually high rates of brain cell proliferation and neurogenesis during adulthood, and the rates of these processes are greatly influenced by the environment. This high level of cell proliferation and its responsiveness to environmental change indicate that such plasticity might be a particularly important mechanism underlying behavioral plasticity in fish. However, as part of their highly labile physiology and morphology, fish also respond to the environment through processes that affect cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 58 publications
3
23
0
Order By: Relevance
“…Enriched environments have been shown to increase the number of new cells in the brains of mammals, of course, both in the hippocampus [Kempermann et al, 1997; for a review, see Kempermann et al, 2010] and, if the olfactory environment was enhanced, in the olfactory bulb [Rochefort et al, 2002;Rochefort and Liedo, 2005]. They have also been shown to increase neurons in the brains of crustaceans [Ayub et al, 2010], insects [Scotto-Lomassese et al, 2000], and fish [Dunlap, 2016]. A recent study also showed enhancement in pigeons given an enriched environment [Melleu et al, 2016], but only in the hippocampus; other areas of the telencephalon showed no effect or even a decrease in cells.…”
Section: Is the Production Of New Cells In The Brains Of Adult Amphibmentioning
confidence: 99%
See 2 more Smart Citations
“…Enriched environments have been shown to increase the number of new cells in the brains of mammals, of course, both in the hippocampus [Kempermann et al, 1997; for a review, see Kempermann et al, 2010] and, if the olfactory environment was enhanced, in the olfactory bulb [Rochefort et al, 2002;Rochefort and Liedo, 2005]. They have also been shown to increase neurons in the brains of crustaceans [Ayub et al, 2010], insects [Scotto-Lomassese et al, 2000], and fish [Dunlap, 2016]. A recent study also showed enhancement in pigeons given an enriched environment [Melleu et al, 2016], but only in the hippocampus; other areas of the telencephalon showed no effect or even a decrease in cells.…”
Section: Is the Production Of New Cells In The Brains Of Adult Amphibmentioning
confidence: 99%
“…In addition, studies on fish by Dunlap and his colleagues [reviewed in Dunlap, 2016] show important effects of social novelty on new cell production. In contrast, group housing without physical enrichment of the environment does not enhance neurogenesis in the dentate gyrus of rats [Brenes et al, 2015].…”
Section: Is the Production Of New Cells In The Brains Of Adult Amphibmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, pop music training also promoted the changes in other cognitive functions of the individual. The plasticity of the brain referred to the ability of neurons to respond to stimuli and make changes (Dunlap, 2016). In addition, the requirements for each type of training were different, so the areas and levels of activation were also different in the training (François et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study (Camara-Ruiz, Santo, Gessner, & Wuertz, 2019), an increase of neuroplasticity markers in fish that were trained to feed prey buried in the sand compared to fish that were not trained was observed. Among these markers pcna, neuroD and bdnf are established markers for neuronal activity and neurogenesis and have been used as tools to understand how external stimuli influence the brain (Dunlap, 2014(Dunlap, , 2016Mes, Krogh, Gorissen, Mayer, & Vindas, 2018). Neuropeptides such as brain-derived neurotrophic factor (bdnf) promote neurogenesis, neuron survival and differentiation as well as synaptic plasticity, thereby modulating the brain in response to the rearing environment (Ebbesson & Braithwaite, 2012;Mattson, Maudsley, & Martin, 2004;Shors, Anderson, Curlik, & Nokia, 2012).…”
mentioning
confidence: 99%